Efficacy of MR vs CT in Epilepsy - Heinz, E. R.; Heinz, T. R.; Radtke, R.; Darwin, R.; Drayer, B. P.; Fram, E.; Djang, William T. (American Journal of Neuroradiology, 1988)
We studied 59 seizure patients with CT, MR, and EEG to determine the efficacy of each in the detection of an epileptogenic focus. EEG was most sensitive (67%), MR was next (53%), and CT was least sensitive (42%). MR detected an abnormality in five patients (8%) in whom CT was negative. EEG was positive in each of these patients. CT failed to demonstrate any focal lesion not detected by MR. MR and CT detected focal abnormalities in seven patients (12%) who had negative EEGs. Five of the seven patients had brain tumors. Eighteen of the 26 patients who underwent surgery had positive CT and MR; 14 of these patients had tumors. The remaining eight patients who had surgery all had temporal lobectomies for intractable seizures; none had tumors. In the complex partial seizure subgroup of 34 patients, MR was positive in 44%, CT was positive in 29%, and EEG was positive in 80%. We consider MR to be the imaging procedure of choice for the detection of an epileptogenic focus in seizure patients. When indicated, CT may be performed as a second procedure to try to distinguish neoplasm from thrombosed vascular malformations and other lesions.